(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Indian Higher Education system is the second largest being expanded over the pastdecades. Educational management which comprises planning, organizing, coordinating, commanding andcontrolling for improving the quality of higher education institutions plays a vital role through variousactivities being performed in this service industry. Most institutions have missions but they may goastray in due course of time and may not be able to measure the successful outcomes of theireducational management processes and related quality outcomes. Benchmarking in education isimportant and can be used for improving administrative processes as well as instructional models atcolleges and universities by examining processes and models at other schools and adapting theirtechniques and approaches. Benchmarking is suitable for institutions of higher education. Forimproving the quality of education and quality principles to be adopted by different institutions asurvey is to be done followed by data analysis for suggesting the quality related aspects in highereducation institutions.